Performance analysis of a finite noncircular floating ring bearing in turbulent flow regime. (July 2017) - Soni, Sandeep; Vakharia, DP
The present paper investigates the turbulence effect on the steady-state performance of a new variety of journal bearing, i.e. the noncircular floating ring bearing. This particular bearing consists of the journal, floating ring, as well as lower and upper lobes. The shaft and the floating ring are cylindrical while surfaces of the bearing are noncircular. The classical Navier–Stokes equations and continuity equation in cylindrical coordinates are being satisfactorily adapted with the linearized turbulent lubrication model of Ng and Pan. These improved equations are being solved by the finite element method using Galerkin's technique and an appropriate iteration strategy. The proposed bearing has a length-to-diameter ratio of 1 and operates over different values of the ratio of clearances (i.e. 0.70 and 1.30). The steady-state performance parameters computed are presented in terms of an inner and outer film eccentricity ratios, load-carrying capacity, attitude angle, speed ratio, friction coefficient variable, oil flow, and temperature rise variable for the Reynolds number up to 9000. The present analysis predicts better performance in the turbulent regime as compared to the laminar regime for the noncircular floating ring bearing.